Mall Patronage Behaviour: Understanding the Inter-Linkages Between Shopping Motives, Shopper Demographics, and Shopping Behaviour - Yadav, Suman; Siraj, Sadaf (Indian Journal of Marketing, 2014)
The retailing sector in India has undergone significant metamorphosis in the past 10 years. Retailing is gradually inching its way towards becoming the next boom industry. Organized retailing has ushered a total transformation of the whole concept of shopping in terms of consumer buying behavior. Shopping today is much more than just buying - it is an experience in itself. The retailing business in India has witnessed a huge growth due to the emergence of supermarkets as well as centrally air-conditioned malls. Consumers are the major beneficiaries of the retail boom. The Indian consumer too is changing rapidly. They now have a choice to choose from a wide range of products, quality, variety, and prices. Consumers are now showing a preference for shopping malls, which enable them to shop a variety of products under one roof and offer a shopping experience in terms of ambience and entertainment. This research tried to examine the impact of shopping motives, demographical profile (age and gender) of shoppers on shopping behaviour: frequency of visits, time spent at the shopping mall, and amount spent on per visit. An attempt was also made to establish a relationship between shopping behaviour and patronage. The study results showed that shopping motives and shopping behavior of the shoppers differed by gender and generation (age group). The results also revealed that shopping behavior (frequency of visits and time spent at the shopping mall) had a positive relationship with patronage behaviour.